Resilience in cogeneration systems: Graphical analysis of novel indexes and system behavior under failure scenarios - da Silva, Fellipe Sartori [UNESP]; Lessa, Thiago Magalhães [UNESP]; Matelli, José Alexandre [UNESP] (Elsevier, 2025)
With the increasing frequency and severity of disasters threatening energy systems, resilience has emerged as a crucial concept in the energy field, addressing the consequences of high-impact, low-probability (HILP) events. Despite its importance, there remains a lack of consensus on how to assess resilience, with energy generation systems, particularly thermal power plants, receiving limited attention in existing investigations. This study advances the development of a robust method for resilience evaluation in energy generation systems through an innovative graphical analysis applied to four cogeneration plants. The proposed method introduces two novel parameters: operability and generation indexes. The decay curves of the operability index reveal an initial downward curvature followed by an inflection point, while the generation index exhibits a sharp decline during the first hours of operation. Efforts to enhance resilience in the early design phase should focus on mitigating these patterns. The derivatives of the curves identified key periods of operational instability, specifically, the initial phase and the most degrading periods. Improved system conditions reduced these instabilities by minimizing the amplitude of the derivative peaks. By integrating the curves, the relative area under the graphs was quantified, revealing that the studied configurations utilizing gas turbines experienced greater sensitivity to HILP events. These findings underscore the importance of proactive resilience strategies tailored to the design and operational characteristics of energy systems.